HABITUS COMPARASION, GROWTH PATTERN AND CONDITION OF CONVICT CICHLID (Amatitlania nigrofasciata GUNTHER, 1986) IN THREE LAKES ECOSYSTEMS IN BALI - Parawangsa, I Nyoman Yoga; Tampubolon, Prawira Atmaja; Saputra, Dewa Gde Tribodhi; Pertami, Nyoman Dati (BAWAL Widya Riset Perikanan Tangkap, 2023)
Convict cichlid (Amatitlania nigrofasciata) belonging to the Cichilidae family has inhabited in Tamblingan Lake, Buyan Lake and Beratan Lake. The existence of this fish species is suspected due to accidental introduction activities. The aims of this study ware to reveal differences in habitus, growth patterns and conditions of convict cichlid in the three lakes on the island of Bali. Samples of convict cichlid were taken by bubu traps, that placed in the littoral zone of the lake. 19 morphometric characters were measured using a digital caliper, then each fish sample was weighed. The growth pattern and condition of convict cichlid are known by using the equation of the length-weight relationship and the condition factor. There were 888 individuals of convict cichlid caught during this study, consisted of 385 fish from Tamblingan Lake, 371 fish from Buyan Lake, and 132 fish from Beratan Lake. Moreover, 108 fish consisting of 36 fish from each lake were further analyzed by measuring 17 additional morphometric characters. The results of measuring the morphometric characters of the observed convict cichlid had different variations for the characters of head length and predorsal length. There was diversity for several morphometric characters of the convict cichlid in Buyan Lake which are a collaboration of characters between the convict cichlid in Tamblingan Lake and in Beratan Lake, namely on the basic characteristics of the anal fin, dorsal fin base, body length, postorbital length, and tail height. The growth pattern of this species in the three lakes was negative allometric and the condition of this fish species was in good condition with the average value of condition factor ranging from 0.95–1.05.